Scientific Tradition and Development of The Qur'anic exegesis in Aceh - Muhammad Amin; Muhammad Reza Fadil; Syafieh Syafieh (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
As the initial gateway for the entry of Islam to the archipelago, Aceh stores much historical information on the spread and development of Islamic teachings. One of the interesting things to study is the development of the field of the Qur'anic exegesis which has experienced rapid development throughout the history of the spread of Islamic teachings in Aceh. By doing a literature study and descriptive analysis method. The result is that the development of the Qur'anic exegesis in Aceh is divided into three periodizations. First, the classical period in which the teaching of the Qur'an did not stand alone but was inserted between the teaching of fiqh and Sufism and delivered ijmali (global) by preachers from Arabia and India. Second, the middle period in which educated Acehnese began to study in Mecca and Medina so that they were proficient in religious knowledge so that the Malay the Qur'anic exegesis of Tarjumān al-Mustafīd by Abdurrauf al-Sinkily was born. Third, the modern period where at this time the works of commentary in Aceh began to develop rapidly, including Al-Qur'ānul Majīd An-Nūr written by Muhammad Hasbi ash-Shiddieqy, Al-Qur'ānul Karīm and Free Translation of Rhymes by Tengku Mahyiddin Yusuf, Tafsir Gayo by Abdurrahman Daudy, and Tafsir Pasee by TH Thalhas, Hasan Basri, Zaki Fuad, A. Mufakhir Muhammad, and Mustafa Ibrahim.